Dimensi Politik Gerakan Perempuan: Suatu Survey - Machya Astuti Dewi (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Survey of literature on women movement which takes place in different places in the world shows us that the movement means different things to different group of people. While the survey tells us that political setting highly influencial in shaping the movement, the very political nature of the movement is not necessarily lays in women relationship to the state. The jargon is that "personal is political." Some movement aims at practical change and other concerns with strategic change. In an attempt to map out the reason, as to why woman movement take place, this article identifies two possible reasons. First, the movement is organised in response to the abusive use of authority. If the movement is not organised in response to authoritarianism it could be taking place in response to the opening of opportunity structure.